Pelatihan Optimalisasi Penggunaan Kit IPA Sains Untuk Meningkatkan Penguasaan Konsep IPA Bagi Guru Guru SD Negeri 1 Cakranegara - I Wayan Gunada; Sutrio Sutrio; Wahyudi Wahyudi; Ahmad Busyairi; Ni Nyoman Sri Putu Verawati; Syahrial Ayub; Kosim Kosim (Unram Journal of Community Service, 2022)
Training on optimizing the use of Science Kits for teachers of SD Negeri 1 Cakranegara has been carried out offline. This training activity aims to train and improve understanding and knowledge using the Science Kit in the learning process so as to improve mastery of science concepts. The methods used are lecture, simulation, and mentoring methods, and at the end of the activity an evaluation is carried out. The expected outcome is that teachers can use the Science Kit in the learning process in the classroom. The results of the activity show that this training activity can increase the knowledge of teachers in assembling and skills using the Elementary Science Kit, so that it has implications for increasing mastery of the concept of science through experiments